Analisis Sentimen Mengenai Kualitas Layanan Jasa Ekspedisi Shopee Xpress Pada Media Sosial Twitter - Tri Widarmanti; Aisyah Munisera (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Technological advances in Indonesia has developed rapidly so that it cannot be separated from people's lives. This technological advancement has had a significant impact on e-commerce and increased usage of delivery services. The more shipping services available, the tighter the competition will be, so the freight forwarders must prepare well if they want to survive in this business competition. Shopee Xpress is one of the expedition services in Indonesia which was developed directly by Shopee so that every package that uses this expedition will be sent and handled directly by the official team from Shopee. However, many customers complain about Shopee Xpress expedition services regarding late delivery, untracked, damaged or lost packages and unfriendly employees. This study aims to understand consumer opinion on the quality of Shopee Xpress services on Twitter using positive and negative sentiments. Research data was collected for 3 months from 01 November 2022 to 30 January 2023. The data obtained was then processed using the NaÃ¯ve Bayes Classifier algorithm with a sentiment analysis method based on the dimensions of service quality. The word cloud is used to describe the words that appear most frequently in each dimension of service quality based on their sentiments. The results show that the model produces an accuracy value of 86.33% which indicates that the model has described the accuracy of the data properly and is valid. Negative sentiment dominates consumer opinion regarding Shopee Xpress with the reliability dimension being the most discussed. Furthermore, based on word cloud visualization, there are several things that consumers often complain about in each dimension as a material for consideration to improve the quality of Shopee Xpress services. The results of research related to Shopee Xpress consumer opinion on Twitter social media can be used by the company as material for consideration to improve and improve the quality of services provided in order to maintain customer loyalty.